Democracy In Al-Qur'an Perspective: Analysis Of Tafsir Maudhu'i Al-Qurthubi and Quraisy Shihab on Verse Ali-Imran 159 - Adilla Fadila Nasrulloh; Rafi Ahmad Fansury; Rahmah Fauziah; Asep Abdul Muhyi (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2024)
The Quran teaches principles to uphold unity, brotherhood, equality and freedom in society. Democracy, although controversial among Muslim intellectuals, values human rights, participation in decision-making, and equality under the law. In Indonesia, democracy is considered a strong basis for society, where the government must obtain the consent of the majority and ensure that the rights of minorities are respected. These principles should be reflected in a form of state that is in line with the values of the majority of its people and provides space for dissent. The purpose of this study is to find out what democracy is in Islam and how democracy is in the perspective of Tafsir Al-Qurthubi and Tafsir Al-Mishbah. The method used in this research is that this research uses descriptive method and also uses maudhu'i interpretation method. The results of this study state that democracy in Islam is taken from Q.S Ali Imran verse 159. In the verse mentioned a fragment of a word also called shu'ara or deliberation which then the word has experienced a development of meaning. The original meaning is bees that drink honey and its meaning after experiencing expansion becomes